Sharia Pharmacy in the Perspective of the Qur'an: An Analysis of Verses About Medicine - Toni Ardi Rafsanjani; Riana Putri Rahmawati; Muhammad Abdur Rozaq (Walidem Institute and Publishing (WIP), 2025)
Objective: This study aims to explore the concept of Sharia pharmacy from the perspective of the Qur'an by analyzing verses related to medicine. Sharia pharmacy represents a pharmaceutical approach integrating scientific aspects with Sharia principles, such as halal, cleanliness, and medical ethics. Theoretical framework: The theoretical framework is grounded in the thematic interpretation (tafsir maudhu’i) of Qur'anic verses, emphasizing their linguistic, historical, and scholarly interpretive contexts. Literature Review: A thorough literature review examines previous studies on Qur'anic perspectives on medicine and their alignment with contemporary pharmaceutical practices. Methods: The research employs a literature study using thematic interpretation to deeply analyze relevant Qur'anic verses alongside medical and pharmaceutical literature. Results: Key findings include the identification of fundamental principles in the Qur'an regarding health, such as maintaining well-being (QS Al-Baqarah: 195), avoiding prohibited substances (QS Al-Maidah: 3), and emphasizing natural remedies (QS An-Nahl: 69). This study also highlights the synergy between Sharia pharmacy concepts and modern pharmaceutical developments, particularly in promoting halal and thayyib (pure and good) products. Implications: The research's implications underline the significance of integrating Sharia values into pharmaceutical science, urging policymakers to prioritize halal certification for pharmaceutical products, especially in Muslim-majority countries. Furthermore, this integration offers a framework for enhancing ethical and spiritual considerations in health services, benefiting both professionals and patients. Novelty: The novelty of this research lies in its comprehensive integration of Qur'anic interpretation with modern pharmaceutical science, offering a fresh perspective on Sharia pharmacy development. This approach enriches the field by bridging spiritual and scientific domains, fostering holistic healthcare solutions. This study serves as a valuable reference for researchers, academics, and pharmacy practitioners aiming to harmonize Islamic values with contemporary pharmaceutical advancements, thereby contributing to better health services globally.